Generation of photonic entanglement in green fluorescent proteins - Siyuan Shi (Nature Portfolio, 2017)
Quantum-enhanced applications such as quantum spectroscopy of biological samples could take advantage from in situ generation of quantum states of light. Here, the authors characterize polarization-entangled photon states generated through spontaneous four-wave mixing in enhanced green fluorescent proteins.